Oncocytic papillary renal cell carcinoma (OPRCC): 2 case report and literature review - Wang, Yanchen; Guan, Lihui; Liu, Yaming; Liu, Yuxuan; Guo, Xiaoyan; Sun, Yaofei (Frontiers in Oncology, 2025)
Oncocytic papillary renal cell carcinoma (OPRCC) is a new papillary renal cell carcinoma (OPRCC) added to the 2016 WHO Classification of Tumors of the Urinary and Male Reproductive System. It is a subtype of carcinoma, PRCC, which is very rare and it is very characteristic and interesting. The morphology, immunophenotype, genetic characteristics and prognosis of OPRCC are uncertain, so the diagnosis and post-operative management of OPRCC are challenging. Recently, two patients with OPRCC have been treated in our hospital, both of whom have undergone surgical treatment. The information of these two cases is described as follows, and the literature is further reviewed to share the current diagnosis and treatment characteristics of OPRCC and the research progress after surgery. At the same time, the diagnosis of OPRCC disease is subdivided from PRCC disease, and the diagnosis of OPRCC disease is more precise. To optimize the individualized management of patients with renal cell carcinoma in order to improve the understanding and diagnosis of the disease.